Analysis of the Feasibility of Business Idea Application Services Online Workshop "OT Repair" Specifically for Tire Repair and Oil Change in the Province of DKI Jakarta - Muhammad Rizal; Ruslaini Ruslaini; Andrew Subhana (Jurnal Ad'ministrare, 2022)
Transportation vehicles are an important aspect for people in DKI Jakarta to support their daily activities by using private vehicles, both motorbikes and cars. While busy in activities, sometimes vehicle owners forget to check the condition of the vehicle, especially routine tire condition checks and oil changes which then have an impact on vehicle engine damage. The OT Repair business idea is a workshop service business innovation that is presented in the form of an application that focuses on tire and oil repair or replacement services. Through the OT Repair application, vehicle users can use repair services through the application, including booking schedules and choosing the nearest repair shop. This study aims to find out whether the OT Repair business idea is the answer to the needs of the people in DKI Jakarta. Qualitative analysis is used in analyzing non-financial feasibility such as marketing aspects, technical aspects as well as management and legal aspects. Quantitative analysis is used to analyze OT Repair business ideas that can meet community needs and feasibility based on investment criteria. The financial aspect shows the BEP is Rp. 410,636,079, the NPV is Rp. 80,767,898, the IRR is Rp. 13%, a PI of 1.16 and a payback period of 3 years and 3 months. The results of this feasibility analysis show that the OT Repair business is feasible based on market and marketing, technical, and management as well as financial aspects. However, it is not feasible based on legal aspects until the process of establishing the legal entity is carried out.